Asuhan Kebidanan Komprehensif pada Ny. K Umur 27 Tahun G2P1A0 di PMB Bidan N - Kasari, Miki; Isfaizah (Universitas Ngudi Waluyo, 2025)
Continuity of care is the provision of midwifery care starting from pregnancy, childbirth, postpartum, neonates until deciding to use family planning (KB). This aims to assist, monitor, and detect the possibility of complications that accompany the mother and baby from pregnancy until the mother uses KB. The method of midwifery care at PMB Bidan N is through home visits by providing counseling according to the mother's needs. Midwifery care provided to Mrs.